Gerakan struktur dan kaitannya dengan faktor kendali tektonik, berdasarkan analisis stratigrafi; Studi kasus geologi kuarter terhadap fase perkembangan Danau Tondano purba sepanjang Remboken - Kakas, Kec. Remboken dan Kec. Kakas, Kab. Tomohon, Sulawesi Ut - Moechtar, Herman; Pratomo, Indyo; Mulyana, Herman; Poedjoprajitno, Soemantri (Geological Agency, 2007)
http://dx.doi.org/10.17014/ijog.vol2no3.20075Studies of stratigraphy on Quaternary deposits in the southwest region of Lake Tondano, Tomohon Regency, South Sulawesi, revealed six facies of deposition environments. These facies consist of Tondano tuff, young volcanic eruption, lake, sand lake, tidal lake, and swamp deposits. Based on the correlation of the lateral and vertical variation of the Quaternary deposits, three unit of the depositional facies were recognized (UFP I-III). Each of the depositional facies unit is characterized by variation of the depositional environment changes which were controlled by tectonics, and was followed by the activity of Sonder main fault. The Sonder main fault activity, which controlled the depositional environment changes was recorded as an UFP. Probably, the character of this stratigraphy could be called as cyclo-tectonostratigraphy. The study was based on analyses of sedimentology and stratigraphy of six borehole information obtained along the E-NW traverse which is approximately parallel to the shorelines of the southwestern part of Lake Tondano. The penetration of the borehead varied from 1.20 to 8.7 m. Â